Empirical Study on the Development of ESS-Based Electric Propulsion System for a Catamaran USV - Uinam Son; Jong-Su Yoon; Jun-Ho Huh; Jin-Hun Choo (IEEE Access)
Autonomous underwater vehicles (AUVs) have been developed and used in research to perform various tasks such as marine surveys and the collection of bathymetric data in certain areas that are difficult for humans to access, such as deep seas. Because AUVs are limited in terms of their execution of tasks that require an extensive amount of energy, unmanned surface vehicles (USVs) and launch and recovery systems (LARS) are jointly used for the transport to task sites as well as the launch and recovery. To comply with international environmental regulations, there are ongoing attempts to reduce the generation of pollutants in USVs. This study focuses on developing an energy storage system (ESS) based power system and electric propulsion system for reducing the pollutants generated by USVs. A USV task scenario is set, and the required power amount is calculated; a power system that satisfies the required power is also configured. Furthermore, an energy management system (EMS) is designed and produced for monitoring and controlling the configured system. The performance is verified through a land experiment by designing and producing the components of the configured ESS-based electric propulsion system. The verified system is installed on a catamaran USV, and a field test was performed in the West Sea of Korea. The load required for propelling a catamaran USV having a length overall (LOA) of 11 m is analyzed through a marine field test, and the effects of a steering function of a vessel on the main thruster system are examined.